Piece is glued in pulling of tubular product tractor - YANG ZHENGFA; GUO CHEN'GANG; YAO YOUFU; LU JUNHU (2015)
The utility model discloses a piece is glued in pulling of tubular product tractor, include the metal fixed block, be fixed in the gluey piece of exerting pressure on the metal fixed block, exert pressure and glue the piece including fixing the butadiene styrene rubber substrate and the organo -silicone rubber layer of setting at the butadiene styrene rubber substrate surface on the metal fixed block, one side of the relative butadiene styrene rubber substrate in organo -silicone rubber layer is equipped with a plurality of archs, be equipped with on the opposite face of butadiene styrene rubber substrate with this arch assorted pit, the bottom of pit is equipped with the adhesive, and it is exactly that a part of surface of gluing the piece to pull gluey main contact surface with tubular product, will pull gluey here and divide into the better butadiene styrene rubber substrate of wholeness ability and set up on the better organo -silicone rubber layer of its surperficial heat resistance for refrigerated tubular product is difficult to cause the injury to the whole glue piece that pulls completely yet, increases its life.